Characterization and kinetics of alumina leaching from calcined Akpugo kaolinite for potential aluminum recovery - Ikechukwu A. Nnanwube; Okechukwu D. Onukwuli (South African Journal of Chemical Engineering, 2023)
The kinetics study on alumina leaching from calcined Akpugo kaolinite was considered in this study. The shrinking core model and other relevant kinetic models were used for kinetic analysis of the leaching process. The leaching rate increases with increase in acid concentration, temperature, and stirring rate from 45.0 to 81.5% for acid concentrations of 2 M and 10 M, 44.9 – 83.6% for temperatures of 30 °C and 90 °C, and 45.7 – 82.7 % for stirring rates of 90 rpm and 540 rpm; while it decreases with increase in solid/liquid (S/L) ratio and particle diameter from 82.5 to 46.1% for S/L ratios of 20 g/L and 45 g/L and from 83.5 to 45.2% for particle sizes of <75 µm and <425 µm, respectively. The experimental data fitted into the diffusion through the product layer model while surface chemical reaction was established as the rate-determining step. The activation energy was estimated to be 26.40 kJ/mol while the frequency factor was estimated as 19.99 s−1. About 83.1% alumina was recovered from Akpugo kaolinite from the kinetic study while the overall kinetic constant was estimated as 4.253 s−1. Hence, the kinetic models considered were sufficient to analyze the experimental data.